2013
DOI: 10.1111/obes.12005
|View full text |Cite
|
Sign up to set email alerts
|

On the Applicability of the Sieve Bootstrap in Time Series Panels*

Abstract: In this article, we investigate the validity of the univariate autoregressive sieve bootstrap applied to time series panels characterized by general forms of cross‐sectional dependence, including but not restricted to cointegration. Using the final equations approach we show that while it is possible to write such a panel as a collection of infinite order autoregressive equations, the innovations of these equations are not vector white noise. This causes the univariate autoregressive sieve bootstrap to be inva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…The bootstrap version ofWesterlund's (2007) tests, meant to robustify them against cross-sectional dependence, is based on the univariate autoregressive sieve bootstrap. The latter has been shown bySmeekes and Urbain (2014) to be invalid for data generating processes characterized by strong cross-sectional dependence, as it does not reproduce the long-run covariance matrix of the data correctly.…”
mentioning
confidence: 99%
“…The bootstrap version ofWesterlund's (2007) tests, meant to robustify them against cross-sectional dependence, is based on the univariate autoregressive sieve bootstrap. The latter has been shown bySmeekes and Urbain (2014) to be invalid for data generating processes characterized by strong cross-sectional dependence, as it does not reproduce the long-run covariance matrix of the data correctly.…”
mentioning
confidence: 99%
“…In addition,Palm et al (2011) showed the validity of the multivariate extension of Paparoditis and Politis' block bootstrap procedure for panel unit root tests in dependent panel settings. In contrast,Smeekes and Urbain's (2014) simulation results suggested the occurrence of size distortion in panel unit root tests based on the autoregressive (AR) sieve bootstrap in cross-sectionally dependent panels. This study, however, followsPalm et al's (2011) bootstrap algorithm, the application of which seems to be more appropriate for our data.…”
mentioning
confidence: 76%
“…With regard to the former, the VAR bootstrap scheme becomes infeasible in panel data where the number of cross-sectional units is large and the dimension of the system is too high. With regard to the latter, Palm (1977) shows that any VAR model can be written as a system of ARMA equations for each unit; starting from this consideration and using the results of Kreiss et al (2011), Smeeks and Urbain (2011) describe the AR sieve bootstrap algorithm for panel data. Chang (2004) has proven the validity of the AR sieve bootstrap in the context of panel data if there is only one contemporaneous source of dependence between the units; however, this 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 3 condition is likely to be violated in many empirical applications.…”
Section: Introductionmentioning
confidence: 99%
“…In this work we try to capture a more complex structure, incorporating in the bootstrap procedure the whole error matrix. In the case of panel data with a complex dependence structure, there are two different way to implement a bootstrap scheme: the first one is to apply a vector autoregressive (VAR) bootstrap, which extends the autoregressive procedure to the multidimensional case (Trapani, 2011); the second one consists of a univariate AR sieve bootstrap, with the modification that the residuals are re-sampled jointly across units to preserve the cross-sectional dependence (Smeeks and Urbain, 2011). With regard to the former, the VAR bootstrap scheme becomes infeasible in panel data where the number of cross-sectional units is large and the dimension of the system is too high.…”
Section: Introductionmentioning
confidence: 99%